PERAN PEMERINTAH KOTA PEKANBARU DALAM PENYELENGGARAAN PENDIDIKAN PADA SEKOLAH MENENGAH ATAS SWASTA TAHUN 2014 - Kanisius Suban Keraf; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Education is a major effort in achieving the Indonesian government should a nation that is educating the nation. In the implementation of the education policy of the central government authorizes local governments to dapattercapai policies fairly and equitably. In Riau province, especially the city of Pekanbaru organized by the Department of Education Pekanbaru. Evidence of the implementation of education policy is by increasing the quality of education at all levels of education. On top Middle School should also be. Not only the National High School High School, but also private. Comparable to improving the quality of education, facilities and infrastructure supporting the achievement of quality improvement should also receive attention from the government primarily on Private High School. Therefore, researchers wanted to see and compare the role of the government, especially Pekanbaru City Pekanbaru City Department of Education in the Implementation of facilities and infrastructure of Top Private School puffy in 2014.The purpose of this study is the first, to find out how the government's role in providing education Pekanbaru City on Private High School in 2014. Second, to find out what are the factors that affect the role of Pekanbaru city government in providing education at High School in 2014. Private research this method descriptive qualitative approach. The research location is Private School SMA Santa Maria Pekanbaru, Private High School Youth and Education Office of the city of Pekanbaru. Data collection through interviews as additional data is through observation of researchers, documents, journals, research reports and media / newspaper. Analysis of the data that have been collected using descriptive techniques.Role of Pekanbaru City Department of Education in improving the quality of education in the form of teacher training in cooperation with the Institute for Education Quality Improvement, Provision of Assistance funds Operasioal School, and scholarship. as a coordination center and the center of the spread of information and data collection from any educational institution in the city of Pekanbaru. Limited authority becomes an excuse presented by the Education Office of Pekanbaru. According to the analysis of the author is trasmisi policy failures that caused the policy to be unfair and uneven and occure ketidakmaksimalan in the achievement of policy objectives. As a result the corresponding results of the analysis of all the data collected and interviews to the writer considered the most understand menganai it was discovered that the infrastructure and facilities Private High School in the city of Pekanbaru not be authorized Pekanbaru City Department of Education. The impact of inequality others is happening to the achievement of quality education for benchmarks which can not be equated with one another between the education unit utamnya Private High School in 2014.Keywords: Role of Government Pekanbaru, Pekanbaru City Education Department, Cast Policies